Pengaruh Efektivitas Live Streaming Dan Flash Sale Terhadap Keputusan Pembelian Produk Wardah Pada E-Commerce Tiktok X Tokopedia - Himmatul Aliyah, Hilda; Kartini, Tina (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to study the profound influence of the effectiveness of Live Streaming and Flash Sale on the purchase decision of wardah products on Tiktok x Tokopedia e-commerce. Specifically, this study will analyze the influence of the effectiveness of live streaming partially on the purchase decision of wardah products, analyze the influence of flash sales partially on the purchase decision of wardah products through live streaming and analyze the relationship between live streaming and flash sale simultaneously with the purchase decision of wardah products. This study uses a quantitative approach with a descriptive-verification research type. Data will be collected through a questionnaire designed for 96 respondents, namely consumers aged 18-28 years in Indonesia who have purchased Wardah products through TikTok x Tokopedia. Indicators used for live streaming include host credibility, interactivity, and information quality, while for flash sales include price discounts, promo deadlines, and visual appeal. Purchasing decisions are measured based on purchase frequency, brand preference, and consumer satisfaction. Data analysis will be carried out using multiple linear regression to test the hypothesis that has been executed. The results of the study show that both live streaming and flash sale have a positive and significant influence on the purchase decision of Wardah products, both partially and simultaneously Flash sale is identified as a more dominant factor in determining purchase decisions than live streaming. In management accounting, these two strategies contribute significantly to increased sales and Return on Marketing Investment (ROMI). This research is expected to provide valuable insights for PT. Paragon Technology and Innovation (Wardah) and other business roles in optimizing digital marketing strategies, increasing competitiveness, and being the basis for data-driven decision-making to achieve more effective sales growth in the digital cosmetics industry.